2021
DOI: 10.3389/fphar.2020.598007
|View full text |Cite
|
Sign up to set email alerts
|

S1PR2 Inhibition Attenuates Allergic Asthma Possibly by Regulating Autophagy

Abstract: This study is to investigate the role of Sphingosine-1-phosphate (S1P) in the asthma progression, and the involvement of autophagy. Airway remodeling mice were subjected to the HE, PAS, and Masson staining. Protein expression levels in the tissues, samples and model cells were detected with ELISA, Western blot analysis, and immunohistochemical/immunofluorescent analysis. The S1P2 receptor antagonist JTE-013 decreased the inflammatory cell infiltration and goblet cell production in asthmatic mice tissues. The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…These results unveiled a previously unappreciated ability of neutrophil CC1 to regulate autophagy via the S1PR2/S1PR3 axis. The mechanism by which autophagy may affect different cell types remains controversial ( 46 , 47 ). We utilized pharmacological inhibitors to investigate the impact of S1PR2/S1PR3 signaling on autophagy, with Baf A1–pretreated S1P-stimulated neutrophils exhibiting enhanced LC3B-2/p62 expression and aggravated NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…These results unveiled a previously unappreciated ability of neutrophil CC1 to regulate autophagy via the S1PR2/S1PR3 axis. The mechanism by which autophagy may affect different cell types remains controversial ( 46 , 47 ). We utilized pharmacological inhibitors to investigate the impact of S1PR2/S1PR3 signaling on autophagy, with Baf A1–pretreated S1P-stimulated neutrophils exhibiting enhanced LC3B-2/p62 expression and aggravated NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, administration of JTE-013, a Sphingosine-1-phosphate receptor 2 (S1PR2) antagonist, in a mouse model of OVA-induced chronic airway inflammation and remodeling, decreased inflammatory cell recruitment and mucus production, reduced BAL IL-1, IL-4, IL-5, and serum IgE levels and attenuated collagen deposition and smooth muscle cell-activating proteins in the lungs. JTE-013 effects were accompanied by decreased Beclin-1 levels and LC3II/LC3I conversion and increased p62 accumulation, indicative of dampened autophagy [153].…”
Section: Role Of Autophagy In Allergic Airway Inflammation In Vivomentioning
confidence: 97%
“…Studies have shown that Rac1 plays an important role in the contraction of various smooth muscles, such as bronchial smooth muscle, bladder smooth muscle, and prostate smooth muscle (180)(181)(182)(183). Although both EHT1864 and NSC23766 are Rac1 inhibitors, they have different pharmacological mechanisms in the inhibition of different smooth muscles (182,184,185), and EHT1864 tends to perform better (186,187). In recent years, new Rac1 inhibitors have been continuously developed.…”
Section: General Rac1 Inhibitormentioning
confidence: 99%